Reduction of Extended‐Release Tacrolimus Dose in Low‐Immunological‐Risk Kidney Transplant Recipients Increases Risk of Rejection and Appearance of Donor‐Specific Antibodies: A Randomized Study. Issue 5 (3rd January 2017) - Gatault, P.; Kamar, N.; Büchler, M.; Colosio, C.; Bertrand, D.; Durrbach, A.; Albano, L.; Rivalan, J.; Le Meur, Y.; Essig, M.; Bouvier, N.; Legendre, C.; et al.
Abstract : The aim of this study (ClinicalTrials.gov, NCT01744470) was to determine the efficacy and safety of two different doses of extended‐release tacrolimus (TacER) in kidney transplant recipients (KTRs) between 4 and 12 mo after transplantation. Stable steroid‐free KTRs were randomized (1:1) after 4 mo: Group A had a 50% reduction in TacER dose with a targeted TacER trough level (C0 ) >3 μg/L; group B had no change in TacER dose (TacER C0 7–12 μg/L). The primary outcome was estimated GFR at 1 year. Of 300 patients, the intent‐to‐treat analysis included 186 patients (group A, n = 87; group B, n = 99). TacER C0 was lower in group A than in group B at 6 mo (4.1 ± 2.7 vs. 6.7 ± 3.9 μg/L, p < 0.0001) and 12 mo (5.6 ± 2.0 vs. 7.4 ± 2.1 μg/L, p < 0.0001). Estimated GFR was similar in both groups at 12 mo (group A, 56.0 ± 17.5 mL/min per 1.73 m²; group B, 56.0 ± 22.1 mL/min per 1.73 m²). More rejection episodes occurred in group A than group B (11 vs. 3; p = 0.016). At 1 year, subclinical inflammation occurred more frequently in group A than group B (inflammation score [i] >0: 21.4% vs. 8.8%, p = 0.047; tubulitis score [t] >0: 19.6% vs. 8.7%, p = 0.076; i + t: 1.14 ± 1.21 vs. 0.72 ± 1.01, p = 0.038). Anti‐HLA donor‐specific antibodies appeared only in group A (6 vs. 0 patients, p = 0.008). TacER C0 should be maintained >7 μg/L during the first year after transplantation in low‐immunological‐risk, steroid‐free KTRs receiving a moderate dose of mycophenolic acid. Abstract : This randomized clinical trial compares two different doses of extended‐released tacrolimus 4 months after kidney transplantation in stable steroid‐free recipients and shows that reduction of the tacrolimus dose increases the risk of acute rejection and the appearance of de novo donor‐specific antibodies.